Local strain and defects in silicon wafers due to nanoindentation revealed by full‐field X‐ray microdiffraction imaging. (25th June 2015) - Li, Z. J.; Danilewsky, A. N.; Helfen, L.; Mikulik, P.; Haenschke, D.; Wittge, J.; Allen, D.; McNally, P.; Baumbach, T.
<x xml:space="preserve">Abstract</x> Quantitative characterization of local strain in silicon wafers is critical in view of issues such as wafer handling during manufacturing and strain engineering. In this work, full‐field X‐ray microdiffraction imaging using synchrotron radiation is employed to investigate the long‐range distribution of strain fields in silicon wafers induced by indents under different conditions in order to simulate wafer fabrication damage. The technique provides a detailed quantitative mapping of strain and defect characterization at the micrometer spatial resolution and holds some advantages over conventional methods.